Concomitant chemoradiotherapy with docetaxel and cisplatin followed by consolidation chemotherapy in locally advanced unresectable non-small cell lung cancer - Eroglu, Celalettin (Medknow Publications & Media Pvt Ltd, 2013)
OBJECTIVES: To evaluate treatment results and toxicities in patients who received concomitant chemoradiotherapy (CRT) followed by consolidation with docetaxel and cisplatin in locally advanced unresectable non-small cell lung cancer (NSCLC). METHODS: Ninety three patients were included in this retrospective study. The patients received 66 Gy radiotherapy and weekly 20 mg/m(2) docetaxel and 20 mg/m(2) cisplatin chemotherapy concomitantly. One month later than the end of CRT, consolidation chemotherapy with four cycles of docetaxel 75 mg/m(2) and cisplatin 75 mg/m(2) were administered at each 21 days. RESULTS: Median age of the patients was 57 (range, 30-74). Following concomitant CRT, 14 patients (15%) showed complete and 50 patients (54%) showed partial response (total response rate was 69%). The median follow-up was 13 months (range: 2-51 months). The median overall survival was 18 months (95% confidential interval [CI]: 13.8-22.1 months); local control was 15 months (95% CI: 9.3-20.6 months); progression-free survival was 9 months (95% CI: 6.5-11.4 months). Esophagitis in eight (9%) patients, neutropenia in seven (8%) patients and pneumonitis in eight (9%) patients developed as grade III-IV toxicity due to concomitant CRT. CONCLUSION: Concomitant CRT with docetaxel and cisplatin followed by docetaxel and cisplatin consolidation chemotherapy might be considered as a feasible, and well tolerated treatment modality with high response rates despite the fact that it has not a survival advantage in patients with locally advanced unresectable NSCLC.